Roots, Heads, or Both? Categorizing Turkish Derivational Affixes - Eniz OĞUZ (Dilbilim Araştırmaları Dergisi)
The categorization of derivational affixes has received well-deserved attention in Distributed Morphology. In addition to single-categorization views that classify derivational affixes as either roots or heads,a recent proposal argues that such units can be both roots and heads. While thiscategorization has been shown to explain Dutch and English data, whether itapplies to different languages has not been extensively investigated. In order toinvestigate the applicability of this recent proposal to the Turkish language, thisstudy examined Turkish derivational suffixes in terms of their stress, flexibility,selection, and ordering patterns. The results showed that the proposal cannotaccount for the patterns of derivational suffixes in Turkish.